Analysis of the utilization, processes, and outcomes of inpatient mental healthcare during the first three waves of the COVID-19 pandemic in the federal state of North Rhine-Westphalia, Germany - Zielasek, Jürgen; Lehmann, Isabell; Vrinssen, Jürgen; Gouzoulis-Mayfrank, Euphrosyne (Frontiers in Psychiatry, 2022)
Abstract Background During the first phase of the Coronavirus-19 disorder (COVID-19) pandemic in the spring of 2020, utilisation of inpatient mental healthcare was significantly reduced. We now report on a long-term observational study of inpatient mental healthcare in a large psychiatric hospital association in Northrhine-Westphalia, Germany, covering the second and third pandemic waves of autumn and winter 2020 followed up until June 2021. Objectives Analysis of the changes of inpatient and daypatient mental healthcare utilisation in an association of psychiatric hospitals during the COVID-19 pandemic from January 2020 until June 2021. Materials and Methods We used the statistics database of the association of the nine psychiatric hospitals of the Rhineland Regional Council (Landschaftsverband Rheinland, LVR). We compared the case numbers of the pandemic period with previous years and analyzed changes in the diagnostic spectrum, rates of coercion and therapeutic outcomes. We also analyzed age, gender, diagnoses and coercive measures of patients tested positive for COVID-19 during inpatient psychiatric healthcare. Results Case rates were reduced during and after the COVID-19 pandemic episodes of 2020 and the following months of spring and summer 2021. Changes varied between diagnostic groups, and there were even increases of case numbers for acute psychotic disorders. Coercive measures increased during the pandemic, but therapeutic outcomes were maintained at the pre-pandemic level. Women and patients of higher ages were overrepresented among psychiatric inpatients with COVID-19. Conclusions The COVID-19 pandemic led to overduring reductions of inpatient psychiatric hospital admissions and changes of the diagnostic spectrum accompanied by increased rates of coercive measures. These effects may reflect an overall increased severity of mental disorders during the COVID-19 pandemic, deferrals of inpatient admissions or a lack of outpatient mental healthcare services utilisation. To differentiate and quantitate these potential factors, further studies in the general population and in the different mental healthcare sectors are needed. In order to reduce the number of COVID-19 cases in psychiatric hospitals, vaccination of people of higher ages and with dementias seem to be the most needed strategy.